Attraction systems for the directional elements in visual art in the works of Bridget Louise Riley – a model (Al-Academy, 2025)
The aim of this research is to explore the strategy of "art for art's sake" in several contemporary visual art styles. To address this, we differentiate between the role of art in terms of the content of the idea and the content of the subject. In the content of the idea, we examine imagined visual perceptions, and it is possible to distinguish between real perceptions and imagined ones. Among the imagined perceptions, we differentiate between several types according to their sources: either from the imagination, a dream illusion, or a visual illusion that appeared in unfamiliar circumstances.In the source of imagined visual perceptions, we encounter perspective drawing. geometric drawing, and kinetic illusion in the Op Art style. In Op Art, we see meticulously crafted linear or geometric compositions executed by talented artists. Their work reveals, to the viewer, a fleeting, oscillating movement in parts of a second, as the viewer's eye focuses on the piece. This is due to the eye receiving the work's structure more slowly than it is presented, leading to a misinterpretation of the vision, manifested in the form of motion. This type of illusion is a visual phenomenon that occurs under unusual circumstances.Pioneers of Op Art flourished in the mid-20th century, including figures such as Victor Vasarely and Bridget Riley. They were followed by many other artists, including Francis Celentano, Marina Apollonio, and Josef Albers. Among the research findings are:Op Art demonstrated formal content designed to captivate the viewer's attention.Bridget Riley benefited from the integration and alternation of lines with directional changes, achieving a visual stimulation that reveals the aesthetic goal of "art for art's sake" through perceived motion, with effects of slowing and speeding.